Flecainide sebagai Antiaritmia untuk Fibrilasi Atrium dan Aritmia Lainnya - Clement, Lyon (Cermin Dunia Kedokteran, 2024)
Atrial fibrillation (AF) is one of the most common arrhythmias globally, and its prevalence is projected to increase, including in Indonesia. AF progression is related to lower quality of life and less responsive to therapy or even becomes irreversible. The progression of AF is significantly slower with the rhythm control strategy than with the rate control strategy alone. The options for therapy in Indonesia are limited to amiodarone and propafenone. Amiodarone is one of the most common drugs prescribed for AF rhythm control, but associated with multiple organ toxicities, thus increasing the risk of multiple side effects, especially on long-term usage, potentially leading to drug discontinuation. Flecainide is an antiarrhythmia with a favourable effectiveness and safety profile, especially for AF management, used for acute cardioversion, long-term rhythm control, and as a therapeutic modality for AF with preexcitation syndrome. Flecainide is a potential drug to address the unmet needs of amiodarone as a long-term management for AF.